Safe Sleep Infant Care Practices Reported by Mothers of Twins. (December 2016) - Damato, Elizabeth G.; Haas, Madeline C.; Czeck, Pamela; Dowling, Donna A.; Barsman, Sarah Gutin
Abstract : Background: The high prevalence of prematurity and low birth-weight places twin infants at increased risk for sudden unexpected infant death (SUID) and/or sudden infant death syndrome (SIDS). Risk for these SUID and SIDS is affected by a combination of nonmodifiable intrinsic risk factors and modifiable extrinsic stressors including infant care practices related to sleep. Although adherence to the full scope of American Academy of Pediatrics (AAP) 2011 recommendations is intended to decrease risk, these recommendations are aimed at singleton infants and may require tailoring for families with multiple infants. Purpose: The study describes infant care practices reported by mothers of twins in the first 6 months postpartum. Methods: Mothers caring for twin infants (N = 35) were surveyed online both longitudinally (at 2, 8, 16, and 24 weeks after infant hospital discharge) and cross-sectionally. AAP recommendations (2011) guided survey content. Results: The degree of adherence to AAP recommendations varied over time. For example, mothers of twins reported 100% adherence to placing twins supine for sleep initially, but many reported putting babies on their stomachs for naps as twins became older. Sharing a parent's bedroom decreased over time as did frequency of crib sharing. Fewer than half of mothers offered a pacifier most or all of the time for sleep. Implications for Practice: Opportunities exist for development of an educational program geared specifically for postpartum parents of twins. Implications for Research: Barriers affecting adherence to AAP recommendations and effectiveness of educational programs addressing needs of this unique population need further exploration.